Management of cases that might benefit from radiotherapy: a standardised patient study in primary care - Halkett, Georgia; Jiwa, Moyez; O'shea, C.; Smith, M.; Leong, E.; Jackson, M.; Meng, X.; Spry, Nigel (Blackwell Publishing Ltd, 2012)
The aim of this study was to assess general practitioner (GP) consultations with standardised patients presenting with cancer-related problems that might benefit from radiotherapy. Standardised patient scenarios were constructed with indications for radiotherapy or with side effects of radiotherapy. Six GPs consulted six standardised patients. All consultations were video recorded. Two GPs independently rated the consultation performance using the Leicester Assessment Package (LAP). Each consultation was also assessed by two radiation oncologists to assess specific decisions taken or advice offered to ‘patients’ in each case. The mean duration of consultations was 13 min and 55 s. Three GPs differed significantly (P 0.025) in competencies measured by the LAP, but not as assessed by radiation oncologists. There was no significant difference in LAP scores when reviewed by scenario. However, there was significant differences in the management of the case with prostate cancer (P = 0.005) and data suggest that GPs management of different problems presented varied widely. These data are consistent with the published literature which suggests that in practice not all patients are appropriately advised or referred. There is a need for innovations to support GPs to manage patients who would benefit from radiotherapy.